Young Hoffman Gallery 1976-1979. - Adrian, Dennis; Young, Donald; Hoffman, Rhona; Young Hoffman Gallery, Chicago (Chicago : Young Hoffman Gallery, 1979)
Tuttle, Richard ; Leaf, June ; Renouf, Edda ; Obuck, John ; Umlauf, Lynn ; LeWitt, Sol ; Judd, Donald ; Anderson, Laurie ; Acconci, Vito ; Pozzi, Lucio ; Haas, Richard ; etc.
Engels
boek